The sinusoidal traversable wormhole. - Fu, Ganwei. (2013)
In a baby universe or the universe at a very small scale, the geometry of space-time is believed to exist as a foamy structure; a term called quantum foam first suggested by John Wheeler. This final year thesis report explores the properties of a sinusoidal traversable wormhole and attempts to solve for the existence of a safe geodesic on the wormhole that elementary particles are able to move about. The aim of this thesis is to achieve a safe geodesic elementary particles may travel on during the very beginning of the formation of the universe.